2019
DOI: 10.3390/pharmacy7020057
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacists’ Knowledge Regarding Drug Disposal in Karbala

Abstract: Background: Consumers and caregivers should remove expired, or unwanted, medications to minimize the chance for misuse or accidentally using those medicines. This study investigated pharmacists’ knowledge regarding drug disposal in Karbala, Iraq. Methods: This study was a cross-sectional survey among pharmacists in Karbala. It was performed from December 2018 until January 2019. A standardized, 12-item, self-administered questionnaire was designed, developed and validated to assess pharmacists’ knowledge when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 15 publications
(26 reference statements)
1
15
1
Order By: Relevance
“…In the current findings, pharmacists disposed UMs mostly in trash followed by burning and disposal by drug wholesalers. These practices are similar to the practices followed by the public in Iraqi and Kuwait [12,13]. The disposal pattern of various dosage forms revealed inconsistency in disposal practices across the various drug dosage forms.…”
Section: Discussionsupporting
confidence: 53%
“…In the current findings, pharmacists disposed UMs mostly in trash followed by burning and disposal by drug wholesalers. These practices are similar to the practices followed by the public in Iraqi and Kuwait [12,13]. The disposal pattern of various dosage forms revealed inconsistency in disposal practices across the various drug dosage forms.…”
Section: Discussionsupporting
confidence: 53%
“…Moreover, flushing unused medications down the toilet or sink, especially liquid dosage forms, has been reported in a lot of studies from a number of countries such as United States [53][54][55]59], England [21][22][23], New Zealand [20], Bangladesh [34], Iraq [60], and Saudi Arabia [51]. In contracts, the sewer method of disposal was less common in Sweden [17], Romania [29], or Oman [61].…”
Section: Literature Review Of Some Reported Disposal Practices Aroundmentioning
confidence: 99%
“…There is, also, an absence of socioeconomic status in many studies. In addition, some of surveys were not conducted in public, but in specific places such as pharmacies (in Iraq) [60] or companies (in Turkey) [24].…”
Section: Literature Review Of Some Reported Disposal Practices Aroundmentioning
confidence: 99%
“…Another reason for increased pharmaceutical waste is a lack of knowledge regarding medication usage and disposal [ 46 , 47 ]. Patients may not be educated as how best to safely dispose of their medicines.…”
Section: Resultsmentioning
confidence: 99%
“…Research on hospitals in Kuwait found that pharmacists lacked knowledge about the consequences of sub-optimal/unsafe pharmaceutical disposal methods and often did not follow guidelines that were issued by the Ministry of Health [ 49 ]. A similar study [ 47 ] on Iraqi hospitals found that pharmacists needed programmes to improve their knowledge of appropriate disposal methods for pharmaceuticals waste. Inadequate training and a lack of awareness among hospital staff, such as nurses and pharmacists, contribute to the increase in pharmaceutical waste in many countries.…”
Section: Resultsmentioning
confidence: 99%